The Effectiveness of Problem-Based Physics Learning to Improve High School Students' Science Process Skills - Ma'ruf Ma'ruf; Ana Dhiqfaini Sultan; Nurzyanti Jani (Jurnal Ilmiah Pendidikan Fisika, 2024)
This research aims to analyze the improvement in students' science process skills after applying the problem-based learning model to physics learning. Physics learning at the high school level, namely at Makassar National High School, experiences several deficiencies in the science process skills experienced by students. Choosing a problem-based learning model can support the delivery of material well. This research uses the problem-based learning model to analyze students' science process skills before and after being taught. The type of research used is quasi-experimental research. The population in this study was 32 students. The sampling technique uses purposive sampling with two classes.  The level of science process skills of class X IPA 2 (experimental) students obtained an average score of 73.60 and class X IPA 3 (control) of 42.81. The results of the N-gain test analysis in the experimental class obtained an average value of 0.59 with medium criteria. The control class had an average N-gain value of 0.05 with low criteria, meaning there was an increase in both classes, so it can be concluded that there was a significant influence on students' science process skills after using the problem-based learning model, The research contribution is that the implementation of problem-based learning is very effective for improving physical science process skills.